Öğretmen Adaylarının “Demokrasi” Kavramına Yönelik Metafor Algıları / Perceptions of Prospective Teachers About the Concept of "Democracy" - İbret, Bilgin Ünal; Recepoğlu, Ergün; Karasu Avcı, Emine; Recepoğlu, Serpil (Journal of History Culture and Art Research, 2018)
ABSTRACT In this study, it is aimed to reveal the perceptions of 4th grade prospective teachers studying in Kastamonu University with respect to the concept of democracy through metaphors. By giving emphasis on common objectives in line with the metaphors students produced, the inferences were made about what they understand from the democracy and direction of their perceptions. In accordance with the nature of the research, qualitative research design "phenomenological pattern" was used. The study group includes a total of 297 prospective teachers who voluntarily participate the study, including 76 men and 221 women girls studying in the fourth class in Kastamonu University Faculty of Education in the 2016-2017 academic year. A survey form, consisted of 1 open-ended question, was used as data collection tool to set students’ perceptions. The participants were asked to fulfil the “Democracy is like …… because …..” expressions featured in the survey form. Data were analyzed with content analysis technique. The data were analyzed by descriptive analysis. In the study, prospective teachers developed 149 different metaphors about the concept of democracy. According to the results obtained in this study, prospective teachers focused on most freedom sun, seesaw, water, balance, tree, equality, bird, life, justice, father, rainbow, sky, shield, breath, train and conscience metaphors. Teacher candidates see the concept of democracy with metaphors that they develop as a factor changing from the point of view. In the study, it was determined that the perception of democracy changed according to gender. In addition, it is seen that prospective teachers perceive democracy as different from each other according to their branches. Öz Bu çalışmada, Kastamonu Üniversitesi’nde öğrenim görmekte olan çeşitli branşlara sahip dördüncü sınıf öğretmen adaylarının demokrasi kavramına ilişkin sahip oldukları algıları metaforlar aracılığıyla ortaya çıkarmak amaçlanmaktadır. Bu amaç doğrultusunda oluşturulan metaforların ortak özellikleri üzerinde durularak, yükseköğretimde öğrenim gören öğrencilerin demokrasi hakkındaki algılarının ne yönde olduğu ve demokrasiden ne anladıkları hakkında çıkarımlar yapılmıştır. Çalışmada nitel araştırma yöntemlerinden birisi olan olgubilim deseni kullanılmıştır. Çalışma grubu, 2016-2017 eğitim öğretim dönemi bahar yarıyılında araştırmaya gönüllü olarak katılmayı kabul eden 221’i kız 76’sı erkek olmak 297 öğretmen adayından oluşmaktadır. Öğretmen adaylarının belirlenen kavramlarla ilgili algılarının ortaya koyulması amacıyla veri toplama aracı olarak, bir adet açık uçlu sorudan oluşan form kullanılmıştır. Çalışmada öğretmen adaylarından “Demokrasi … gibidir; çünkü … .” ifadesini tamamlamaları istenerek veriler elde edilmiştir. Elde edilen veriler betimsel analiz yoluyla çözümlenmiştir. Çalışmada öğretmen adayları demokrasi kavramına yönelik 149 farklı metafor geliştirmişlerdir. Bu çalışmada öğretmen adayları bu metaforlardan en fazla özgürlük, güneş, tahterevalli, su, terazi, ağaç, eşitlik, kuş, hayat, adalet, baba, gökkuşağı, gökyüzü, kalkan, nefes, tren ve vicdan metaforları üzerinde durmuşlardır. Öğretmen adayları geliştirdikleri metaforlarla demokrasi kavramını daha çok bakış açısına göre değişen bir unsur olarak görmektedirler. Çalışmada demokrasiyi algılama biçiminin cinsiyete göre değiştiği tespit edilmiştir. Ayrıca öğretmen adaylarının demokrasiyi branşlarına göre birbirlerinden farklı olarak algıladıkları görülmektedir.